Analisis Kepuasan Pengguna Terhadap Layanan Aplikasi Brimo Pada Mahasiswa STMIK Antar Bangsa Menggunakan Mobile Service Quality dengan Metode CSI - Fajri, Annur; Kurnia Rifki, Arsyad (Jurnal Teknik Informatika, 2025)
Abstract— BRImo offers a variety of services that simplify banking transactions for its users. The issue addressed in this study arises from frequent system disruptions and numerous user complaints regarding the application’s performance, particularly concerning access speed, as indicated by reviews on the Google Play Store. These issues have led to a decline in user interest in the BRImo application. Considering the ongoing complaints and less-than-satisfactory ratings, this research aims to assess user satisfaction with the BRImo application among students at STMIK Antar Bangsa. This study employs the Customer Satisfaction Index (CSI) method to measure the percentage of user satisfaction, with modified dimensions from Mobile Service Quality tailored to the focus of this research. Data were collected through a questionnaire consisting of 15 questions and involving 50 respondents. The collected data were tested for validity and reliability before being processed using the CSI method. The results of this study can be seen in the calculation of the CSI method, the percentage of user satisfaction is 75.78% and it can be stated that customers feel "Satisfied" with the service quality of the BRImo application.